Design and simulation of AIN-Based FBAR Resonator for Hydrogen sulfide Gas detection. - Ba Hashwan, S.S. (Institute of Electrical and Electronics Engineers Inc., 2021)
The mathematical modeling, design, and simulation of the film bulk acoustic resonator (FBAR) sensor based on Aluminum nitride (AIN) thin film for hydrogen sulfide gas detection are presented in this paper. The FBAR sensor is designed according PiezoMUMPs fabrication technology. The mathematical modeling and finite element simulation were performed using MATLAB and CoventorWare software to investigate the FBAR sensor resonant frequency. The resonant frequency monitoring is considered the core principle of the FBAR gas sensor detection mechanism. The fundamental of the FBAR sensor is based on the resonant frequency reduction due to the mass changes of the nanomaterial sensitive layer that coated on the surface of the top electrode induced by hydrogen sulfide gas species absorption. The development of the graphene oxide-copper oxide hybrid thin film as sensitive layer is illustrated and their mass loaded was evaluated in the theoretical calculation. The theoretical calculation of the resonant frequency for the thickness extensional mode of the FBAR sensor was found to be 9.4524 GHz and it was verified using the CoventorWare simulation software which shown an excellent agreement between both calculated and simulated frequencies which found to be 9.4524 and 8.955 GHz, respectively. Â© 2021 IEEE.